Ganglioside GM1 Targets Astrocytes to Stimulate Cerebral Energy Metabolism - Finsterwald, Charles; Dias, Sara; Magistretti, Pierre J.; Lengacher, Sylvain (Frontiers in Pharmacology, 2021)
Gangliosides are major constituents of the plasma membrane and are known to promote a number of physiological actions in the brain, including synaptic plasticity and neuroprotection. In particular, the ganglioside GM1 was found to have wide range of preclinical and clinical benefits in brain diseases such as spinal cord injury, Huntington’s disease and Parkinson’s disease. However, little is known about the underlying cellular and molecular mechanisms of GM1 in the brain. In the present study, we show that GM1 exerts its actions through the promotion of glycolysis in astrocytes, which leads to glucose uptake and lactate release by these cells. In astrocytes, GM1 stimulates the expression of several genes involved in the regulation of glucose metabolism. GM1 also enhances neuronal mitochondrial activity and triggers the expression of neuroprotection genes when neurons are cultured in the presence of astrocytes. Finally, GM1 leads to neuroprotective effect in astrocyte-neuron co-culture. Together, these data identify a previously unrecognized mechanism mediated by astrocytes by which GM1 exerts its metabolic and neuroprotective effects.